BASED ON THE STRESS FIELD INTENSITY APPROACH OF PUMPING UNIT HORSE HEAD FATIGUE LIFE PREDICTION - TANG DongLin; SHEN JieBin; GUO Qiang; SHI Lei; YIN XiaoJing (Jixie qiangdu)
With Nominal Stress Method of pumping unit horse head fatigue life prediction results deviate from the actual,introduction of the Stress Field Intensity Approach,the prediction step of the two methods is given. Based on the cyclic and alternating load analysis of horse head,do static simulation in the ANSYS simulation environment,calculate stress under the ultimate load; do Quasi-static simulation,calculate stress and partial damage regional stress field which changes over time.According to the steps,deal with the simulation results and get the fatigue life prediction of the two kinds of methods. Making count a figure of horse head life and fit the fatigue life distribution to verify accuracy of the two methods,analysis the reason of different result error. The result shows that the Stress Field Intensity Approach forecasting accuracy is higher,predicted result fits the actual.